PATHOGENESIS AND CLINICAL MANIFESTATIONS OF DENTAL DEVELOPMENTAL DISORDERS - Ismatov , Фаррух (International Journal of Scientific Pediatrics, 2024)
This article provides a comprehensive review of the pathogenesis and clinical manifestations of dental developmental disorders, which present significant challenges in modern dentistry. It examines the mechanisms leading to these disorders, focusing on genetic, environmental, and infectious factors that disrupt normal tooth development. Various conditions are discussed, including enamel hypoplasia, dentinal dysplasia, imperfect amelogenesis, and taurodontism, with an emphasis on their etiological roots and impact on oral health. The clinical manifestations of these disorders range from aesthetic defects to functional problems and complications, such as increased tooth mobility and frequent infections. The article analyzes diagnostic methods, including radiography, computed tomography, and genetic testing, which aid in the early detection of pathological changes. Early diagnosis is crucial for effective management and prevention of further complications. The article also explores treatment strategies and management approaches for these conditions, including restorative procedures, orthodontic treatment, and surgical interventions. It underscores the importance of early intervention to improve outcomes and prevent progressive damage. Recommendations for optimizing clinical practice and developing more effective treatment and prevention strategies for dental developmental disorders are provided. The integration of contemporary research and clinical data aims to enhance understanding and management of these complex conditions.